1999
DOI: 10.1007/978-3-662-03864-2
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Pollution Prevention

Abstract: Industrial pollution prevention: with 14 tables / Thomas T. Shen. -2., completely rev. and enl. ed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The techniques used in P2 [1] to improve the process are essentially waste minimisation and adoption of cleaner technologies. The former seeks means to reduce pollution at source (Fig.…”
Section: Reduction At Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…The techniques used in P2 [1] to improve the process are essentially waste minimisation and adoption of cleaner technologies. The former seeks means to reduce pollution at source (Fig.…”
Section: Reduction At Sourcementioning
confidence: 99%
“…Progress in the understanding of the phenomena of pollution and modifications to the eco-system has revealed that today's problems are the result of past decisions and that environmental impacts must be seen from a product and process design point of view and over the long term [1,2]. Moreover, the ability of some companies to exploit the environmental issue as a competitive advantage has turned eco-efficiency in an opportunity to improve production process performance by means of new cleaner technologies, process modifications and appropriate management practices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the chemical industry, pollution can be prevented successfully by modifying production processes with the adoption of more advanced technologies through process variable controls, changing cleaning processes, changing chemical catalysts, or by segregating and separating wastes, based on different characteristics of matter (boiling or freezing points, density, solubility, etc.) to name only a few [6]. New technologies for the firm can also incorporate end-of-the-pipe technologies which offer definite advantages to some firms because of their greater, short-term adaptability, in comparison with more radical (cleaner) process innovations.…”
Section: Resultsmentioning
confidence: 98%